Development of novel ultrasonic temperature measurement technology for combustion gas as a potential indicator of combustion instability diagnostics. (August 2019) - Hwang, Ouk; Lee, Min Chul; Weng, Wubin; Zhang, Yuhe; Li, Zhongshan
Highlights: A novel ultrasonic thermometry for flame was developed. Temperature of combustion gas above the multi-jet burner was measured. Temperature was measured at a rate of 1000 samples/s with 0.73% uncertainty. This fast measurement enables the diagnosis of combustion instability. Temperature measured by two-line atomic fluorescence and thermocouple was compared. Abstract: In this study, a high-speed, fast responsive, non-intrusive ultrasonic thermometry system was proposed as a potential candidate for overcoming the disadvantages of thermocouples. The principle of this system is based on the thermal dependence of the speed of sound, and the temperature is measured by detecting the flight time of ultrasonic wave (USW) between the transmitter and the receiver. For a fast and exact measurement, the algorithm was developed as simple as possible, and the exact values of the physical properties, such as specific heat ratio and molecular weight of combustion gas, were taken from the computational calculation of CHEMKIN-Pro with GRI 3.0 mechanism. The performance of the system was verified by two experiments. First, the system was applied to measure the temperature of heated air. Results showed high precision with a 0.3% error when incorporating a modification equation and fast responsive dynamic performance, which directly reflect the rapid temperature change. Second, the combustion gas temperature above a multi-jet burner, which provides a horizontally uniform temperature distribution similar to a flat flame burner, was measured. Five different flame temperatures were measured using a thermocouple and an optic-based measurement method based on two-line atomic fluorescence (TLAF) as well as ultrasonic thermometry to compare their performances. Ultrasonic thermometry showed a slightly lower accuracy than those of TLAF and the thermocouple. This condition could be overcome by correcting the results using linear fitting, as the temperature measured by USW showed the best linearity among them. The USW technique showed excellent performance in terms of the measurement speed of 1000 samples/s and uncertainty under 0.73%. This USW thermometry of combustion gas can be applied to many combustion systems, including boilers and gas turbines. Specifically, fast temperature measurement at a speed of around 1 kHz enables the diagnosis of the combustion instability phenomenon, which is a difficult task when using conventional methods of temperature measurement. Furthermore, both dynamic pressure and temperature can be simultaneously measured at a high rate, thus synergistically increasing the accuracy of combustion instability diagnosis with sufficient information, such as the Rayleigh index or the flame transfer function.